(untitled) (World Bulletin of Education and Learning, 2026)
This paper analyzes the aesthetic meaning and pragmatic functions of phraseological units used in Oscar Wilde’s novel The Picture of Dorian Gray. In the text, idioms and fixed expressions play a significant role in shaping characters, depicting the social atmosphere, and intensifying Wilde’s ironic and critical narrative style. Phraseological units in Lord Henry’s paradoxical speech are especially important, as they influence the reader and act as a persuasive tool that accelerates Dorian’s psychological transformation. At the same time, the phraseology found in Basil’s and Dorian’s speech reflects their inner emotions, moral conflict, and attitudes toward beauty, conscience, and spiritual corruption. The study focuses on how phraseological units acquire aesthetic value through context and how they perform pragmatic tasks such as evaluation, emotional impact, character construction, irony, and manipulation. The research demonstrates that phraseology in the novel is not merely decorative but functions as an expressive device that conveys Wilde’s artistic worldview and the moral problems of Victorian society.